Impacto del Plan Lindt & Sprüngli en la socioeconomía del productor cacaotero tradicional en el cantón El Empalme, provincia del Guayas, 2017 - Méndez Vélez, Jordy Clemente (2017)
The research in question was carried out in order to determine the socioeconomic impact of the Lindt & Sprüngli plan on fine cocoa and flavor producers in the El Empalme canton, province of Guayas, surveying the 31 cocoa producers who benefit from said plan in the area. study. As main results it was observed that the farmers mostly burn the waste of their homes, while the agrochemical containers recycle them, also finance their production with their own funds, selling the oreado grain (87%), having as main marketing problem the low prices (84%), since in its entirety it sells to intermediaries. All producers receive technical advice from the Lindt & Sprüngli program, through which they have increased the implementation of weed control, fertilization, pest and disease control, tool disinfection, cleaning, grain storage and drying, pruning and irrigation. The percentage of farmers who safely store the agrochemicals rose from 65% to 100% with the implementation of the Lindt & Sprüngli plan, in addition this plan has trained farmers in terms of production registration, planning activities, good working relationship, training the staff with more than 90% who have actually put it into practice, and also 84% currently manage the record of income and expenses in their production units, improving their production, price per quintal and income, decreasing costs. The producers consider that the main benefit of the Lindt & Sprüngli plan is the technical assistance that allows them to implement production technologies that significantly help agricultural productivity, preferring that the benefit of $ 3.00 per quintal of cocoa delivered to the collection center, it is done through agricultural inputs (61%), tools (26%) and planting material (13%). The bonus per quintal is an aspect that 28 producers (90%) believe should be improved, while 6 (19%) request the implementation of irrigation systems in their farms, considering that this can help to increase production. The perception that cocoa producers have of the plan is positive considering that production, agronomic management, grain quality, income, cost reduction, quintal prices, marketing, technical assistance and planning of activities, have become between good and very Well, according to your experiences before being in said plan. Key words: Lindt & Sprüngli, cocoa producer, socioeconomic impact.